Exercise-Induced Atrial Remodeling in Female Amateur Marathon Runners Assessed by Three-Dimensional and Speckle Tracking Echocardiography - Lasocka, Zofia; Lewicka-Potocka, Zuzanna; Faran, Anna; Daniłowicz-Szymanowicz, Ludmiła; Nowak, Radosław; Kaufmann, Damian; Kaleta-Duss, Anna; Kalinowski, Leszek; Raczak, Grzegorz; Lewicka, Ewa; Dąbrowska-Kugacka, Alicja (Frontiers in Physiology, 2022)
Endurance athletes have an increased risk of atrial remodeling and atrial arrhythmias. However, data regarding atrial adaptation to physical exercise in non-elite athletes are limited. Even less is known about atrial performance in females. We aimed to elucidate exercise-induced changes in atrial morphology and function in female amateur marathon runners, using three-dimensional (3D) echocardiography and two-dimensional (2D) speckle tracking echocardiography (STE). The study group consisted of 27 female (40 ± 7 years) amateur athletes. Right (RA) and left atrial (LA) measures were assessed three times: two-three weeks before the marathon (stage 1), immediately after the run (stage 2), and two weeks after the competition (stage 3). Directly after the marathon, a remarkable RA dilatation, as assessed by RA maximal volume (RAVmax, 31.3±6.8 vs. 35.0±7.0ml/m2; p=0.008), with concomitant increase in RA contractile function [RA active emptying fraction (RA active EF), 27.7±8.6 vs. 35.0±12.1; p=0.014; RA peak atrial contraction strain (RA PACS) 13.8±1.8 vs. 15.6±2.5; p=0.016] was noticed. There were no significant changes in LA volumes between stages, while LA active EF (34.3±6.4 vs. 39.4±8.6%; p=0.020), along with LA PACS (12.8±2.1 vs. 14.9±2.7; p=0.002) increased postrace. After the race an increase in right ventricular (RV) dimensions (RV end-diastolic volume index, 48.8±11.0 vs. 60.0±11.1 ml/m2; p=0.001) and a decrease in RV function (RV ejection fraction, 54.9±6.3 vs. 49.1±6.3%; p=0.006) was observed. The magnitude of postrace RV dilatation was correlated with peak RA longitudinal strain deterioration (r=-0.56, p=0.032). The measured parameters did not differ between stage 1 and 3. In female amateur athletes, apart from RV enlargement and dysfunction, marathon running promotes transient biatrial remodeling, with more pronounced changes in the RA. Postrace RA dilatation and increment of the active contraction force of both atria is observed. However RA reservoir function diminishes in those with postrace RV dilation.